Amusing Ourselves to Loyalty? Entertainment, Propaganda, and Regime Resilience in China. (December 2022) - Xia, Shouzhi
Is it possible to form "soft autocracy" that manages citizens by taking away their sense of resistance? This paper suggests that the rise of entertainment media in autocracies enables the rulers to maintain their resilience through a soft approach, thereby avoiding costly heavy-handed measures. Such a soft approach can work because entertainment media, like "fictitious pleasure drugs, " undo audiences' sophistication so that people are susceptible to autocratic propaganda. By analyzing a Chinese data set, via instrumented regressions, this paper shows that a one standard deviation increase in people's interest in entertainment media is associated with an increase of almost 20% in both their satisfaction with the current regime and their anti-Western hostility. Furthermore, the findings show a positive relationship between people's entertainment media interest and their acceptation of indoctrination by state media. In short, entertainment media contribute to China's regime stability through "amusing ordinary citizens to loyalty."